Optically pure, structural and fluorescent analogues of a dimeric Y4 receptor agonist derived by an olefin metathesis approach - Liu, Mengjie; Mountford, Simon J.; Richardson, Rachel R.; Groenen, Marleen; Holliday, Nicholas D.; Thompson, Philip E. (American Chemical Society, 2016)
The dimeric peptide 1 (BVD-74D, as a diastereomeric mixture) is a potent and selective Neuropeptide Y Y4 receptor agonist. It represents a valuable candidate in developing traceable ligands for pharmacological studies of Y4 receptors, and as a lead compound for anti-obesity drugs. Its optically pure stereoisomers along with analogues and fluorescently labelled variants were prepared by exploiting alkene metathesis reactions. The (2R,7R)- diaminosuberoyl containing peptide, (R,R)-1 had markedly higher affinity and agonist efficacy than its (S,S)-counterpart. Furthermore the sulfo-Cy5 labelled (R,R)-14 retained high agonist potency as a novel fluorescent ligand for imaging Y4 receptors.